2017
DOI: 10.3892/mmr.2017.7244
|View full text |Cite
|
Sign up to set email alerts
|

Microarray data re-annotation reveals specific lncRNAs and their potential functions in non-small cell lung cancer subtypes

Abstract: Non-small-cell lung cancer (NSCLC) is a leading cause of cancer mortality worldwide. The most common subtypes of NSCLC are adenocarcinoma (AC) and squamous cell carcinoma (SCC). However, the pathophysiological mechanisms contributing to AC and SCC are still largely unknown, especially the roles of long non-coding RNAs (lncRNAs). The present study identified differentially expressed lncRNAs between lung AC and SCC by re-annotation of NSCLC microarray data analysis profiling. The potential functions of lncRNAs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Previous researchers showed similar results concerning the association with the histology type. Scholars recommended that the expression levels of SOX2OT might be a key biomarker to discriminate ADCs from SCCs of the lung . We found an association between TNM stage and SOX2OT expression levels, which was confirmed by ROC analysis, that SOX2OT is a prognostic marker with 80% sensitivity and 76% specificity to discriminate between early and late stages of NSCLC.…”
Section: Discussionsupporting
confidence: 78%
“…Previous researchers showed similar results concerning the association with the histology type. Scholars recommended that the expression levels of SOX2OT might be a key biomarker to discriminate ADCs from SCCs of the lung . We found an association between TNM stage and SOX2OT expression levels, which was confirmed by ROC analysis, that SOX2OT is a prognostic marker with 80% sensitivity and 76% specificity to discriminate between early and late stages of NSCLC.…”
Section: Discussionsupporting
confidence: 78%
“…Around the globe, lung cancer is the leading cause of cancer incidence and mortality, with 2.1 million new lung cancer cases and 1.8 million deaths worldwide (1)(2)(3)(4). Up to 61% of patients with NSCLC had advanced disease at the time of diagnosis, with a 5-years survival rate of 18% (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Comparing to our understanding about microRNAs (miRNA) as a commonly studied ncRNAs, the function of the subset long non-coding RNAs (lncRNAs) is relatively unknown. [ 3 7 ] Small nucleolar RNA host gene 20 (SNHG20) has attracted more attention in the past few years due to its potential role in tumorigenesis. Locating on chromosome 17q25.2 with the length of 2183 base-pairs, SNHG20 was firstly identified in hepatocellular carcinoma (HCC) and subsequent studies suggested that SNHG20 played important roles including colorectal cancer, cervical cancer, and breast cancer.…”
Section: Introductionmentioning
confidence: 99%